2018
DOI: 10.3390/colloids2010001
|View full text |Cite
|
Sign up to set email alerts
|

Microbial-Enhanced Heavy Oil Recovery under Laboratory Conditions by Bacillus firmus BG4 and Bacillus halodurans BG5 Isolated from Heavy Oil Fields

Abstract: Microbial Enhanced Oil Recovery (MEOR) is one of the tertiary recovery methods. The high viscosity and low flow characteristics of heavy oil makes it difficult for the extraction from oil reservoirs. Many spore-forming bacteria were isolated from Oman oil fields, which can biotransform heavy crude oil by changing its viscosity by converting heavier components into lighter ones. Two of the isolates, Bacillus firmus BG4 and Bacillus halodurans BG5, which showed maximum growth in higher concentrations of heavy cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 56 publications
(68 reference statements)
0
15
0
1
Order By: Relevance
“…El-Sheshtawy et al [11] found an 8.6% removal yield of oil in columns of sand using the isolated biosurfactant from C. albicans. Other researchers reported oil recovery yields ranging from 20 to 60%, using biosurfactants produced by different microbial species, such as Bacillus firmus BG4, Bacillus halodurans BG5 [36], Bacillus subtilis [37], and P. aeruginosa [38]. Finally, Batista et al [33] reported that the crude biosurfactant produced by C. tropicalis removed 78 to 97% of motor oil absorbed to sand.…”
Section: Static Assaymentioning
confidence: 99%
“…El-Sheshtawy et al [11] found an 8.6% removal yield of oil in columns of sand using the isolated biosurfactant from C. albicans. Other researchers reported oil recovery yields ranging from 20 to 60%, using biosurfactants produced by different microbial species, such as Bacillus firmus BG4, Bacillus halodurans BG5 [36], Bacillus subtilis [37], and P. aeruginosa [38]. Finally, Batista et al [33] reported that the crude biosurfactant produced by C. tropicalis removed 78 to 97% of motor oil absorbed to sand.…”
Section: Static Assaymentioning
confidence: 99%
“…Microbial enhanced oil recovery (MEOR) is a collection of techniques that utilise microorganisms and their metabolic products to improve the recovery of crude oil from reservoir rock (Yen, 1990;Lazar et al, 2007;Zhang and Xiang, 2010;Shibulal et al, 2014Shibulal et al, , 2018Cui et al, 2019). The recovery can either be in the form of cyclic (single-well simulation), microbial flooding, or selective plugging recovery (Lazar et al, 2007;Shibulal et al, 2014).…”
Section: History Of Biologically Enhanced Oil Recoverymentioning
confidence: 99%
“…Enhanced oil recovery using polymer flooding and microbial enhanced oil recovery can act synergistically to solve the issues that limit efficient recovery process. In order to successfully implement enhanced oil recovery, many groups of researchers have experimentally investigated the feasibility and potential of using novel biopolymers developed through synergistic chemical and microbial technology (BcEOR) (Yen, 1990;Lazar et al, 2007;Zhang and Xiang, 2010;Shibulal et al, 2014Shibulal et al, , 2018Cui et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradation of crude oil by strains of Bacillus bacteria and its applications in breaking down spilled oil are widely reported (Ijah and Ukpe, 1992). More recently, Shibulal et al (2018) showed that heavy oils from various fields in Oman, when treated with the in-situ spore-forming bacteria Bacillus firmus and Bacillus halodurans, could be transformed into lighter oils. Laboratory tests indicated that these bacteria were specifically converting aromatic molecules into aliphatic molecules in the heavy oils treated.…”
Section: Mechanisms Driving Mieormentioning
confidence: 99%